Risk Mitigation Techniques in Agile Development Processes - Rafeek, Muhammad Akil; Arbain, Adila Firdaus; Sudarmila, Endah (International Journal of Supply Chain Management, 2019)
The main purpose of agile development methods is to reduce risks leading to a more successful and effective information system. In fact, analysing priorities, finding and identifying risks are important activities in all development approaches, including Agile development. However, some studies seek to assess risk management based on agile global software development (GSD) and provide mitigation measures to address specific risks. The risk mitigation technique for good development for sustainable development is expected to be designed to achieve time efficiency improvements to obtain greater resources at lower cost and thereby gain and maintain a competitive advantage.